Hemangiosarcoma associated with Chemodectoma in an Old Pit Bull Bitch - Tineli, Tainara Renata; Conte, Fernanda; Strack, Adriane; Menegatt, Jean Carlo Olivo; Ramos, Adriano Tony; Veiga, Angela Patricia Medeiros; Pereira, Marcy Lancia (Acta Scientiae Veterinariae, 2020)
Background: The prevalence of neoplasms in domestic animals has been augmenting over the years. Hemangiosarcoma, which most frequently affects large breed dogs, is a neoplasm with high metastatic power and corresponds to 5% of malignant neoplasms. Chemodectoma, a neoplasm that can have malignant or benign behavior, is uncommon, corresponding to less than 8% of all cardiac tumors, and originates from cardiac chemoreceptor cells and involves mainly the aortic and carotid bodies. The aim of this study is to describe the case of an elderly Pit Bull dog with hepatic hemangiosarcoma and chemodectoma associated with four other different tumors: hemangioma, papilloma, mastocitoma and melanoma. Case: A 14-year-old female Pit Bull, castrated, was presented to Veterinary Clinic of the Federal University of Santa Catarina (UFSC), Curitibanos Campus, Brazil. The owner referred apathy, hyporexia, and increased abdominal volume for two weeks. Physical examination showed emaciation and abdominal effusion. Abdominocentesis was performed, three liters of serosanguineous fluid was drained and a sample was sent for analysis. Complementary tests were requested and showed mild hypoalbuminemia, normocytic normochromic anemia, and lymphopenia. The ultrasound examination revealed thickening of vessels and hepatomegaly, in addition to the presence of an oval structure containing hyperechogenic cavitations. Diagnostic exploratory laparotomy was indicated, but the owner refused. Drug therapy was prescribed in a palliative manner and, during the clinical follow-up period, two abdominocentesis procedures and one thoracentesis procedure were performed, both resulting in simple transudate. Finally, the patient developed severe apathy, edema in all limbs, and died at home. Necroscopic examination was done and revealed hemoperitoneum and hemothorax; several nodules with diverse characteristics in the integument were noted, which were classified by histopathological analysis as follicular cyst, papilloma, cavernous hemangioma, mastocytoma, and melanoma. The histological sections of the liver sample showed hemangiosarcoma and those of the urinary bladder showed hemangiosarcoma metastases. In the heart, a nodule was found at the base of the aorta, which was characterized as chemodectoma. Besides that, there was myxomatous mitral valve degeneration. The necropsy report indicated that the cause of death was hypovolemic shock associated with complications from multiple tumors, particularly hepatic hemangiosarcoma and chemodectoma. Discussion: Hemangiosarcoma is a malignant tumor with invasive behavior. The patient was an elderly Pit Bull dog, a breed not described as being predisposed to this type of tumor. Similarly to other reports in the literature, there was abdominal effusion with rapid and recurrent evolution, progressive weight loss, and metastases in the urinary bladder. It is believed that thoracic effusion, limb edema, and hepatic venous congestion were probably caused by chemodectoma owing to right-sided congestive heart failure. Although not related to the cause of death of this patient, the presence of tumors like papilloma, mastocytoma, melanoma, and hemangioma is noteworthy because the canine had a total of six different types of neoplasms, rarely reported in Pit Bull dogs. This work emphasizes the importance of necroscopic evaluation, which, in this case, was essential for the definitive diagnosis.